Outcomes of endovascular occlusion and stenting in the treatment of carotid blowout - Brinjikji, Waleed (Interv Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Carotid blowout is a life threatening complication of invasive head and neck cancers and their treatments. This is commonly treated with endovascular embolization and carotid stenting. Using the Nationwide Inpatient Sample, we report the immediate clinical results of patients receiving embolization and/or stenting for treatment of carotid blowout associated with head and neck cancer. MATERIALS AND METHODS: Using the Nationwide Inpatient Sample from the period 2003–2011, we defined carotid blowout patients as those with head and neck malignancies receiving carotid stenting and/or endovascular embolization without open surgery. Outcomes studied included mortality, acute ischemic stroke, hemiplegia/paresis, and other post-operative neurologic complications. Outcomes for the endovascular embolization and carotid stenting group were compared. RESULTS: A total of 1218 patients underwent endovascular treatment for carotid blowout. Of these, 1080 patients (88.6%) underwent embolization procedures and 138 patients (11.4%) underwent carotid stenting. The mortality rate of endovascular embolization patients was similar to that of carotid stenting patients (8.0%, 95% confidence interval (CI) = 6.5%–9.7% versus 10.2%, 95% CI=6.0%–16.4%, p = 0.36). Stroke rate was similar between embolization patients and stenting patients (2.3%, 95% CI=1.6%–3.4% vs. 3.4%, 95% CI=1.3%–8.4%, p = 0.43). Hemiplegia rates were significantly higher rate in stenting patients compared with endovascular occlusion patients (3.8%, 95% CI=1.3%–8.4% vs. 1.4%, 95% CI=1.4%–2.4%, p = 0.05). The rate of post-operative neurologic complications was higher in stenting patients compared with embolization patients (6.5%, 95% CI=3.3%–12.1% vs. 1.4%, 95% CI=0.9%–2.4%, p < 0.0001). CONCLUSIONS: Given the natural history of carotid blowout, carotid stenting and endovascular embolization are acceptable means of treating this disease. Endovascular embolization remains the most common treatment among patients with head and neck cancers with lower overall rates of post-operative neurologic complications, including hemiplegia/paresis and stroke.